Knockdown of lincRNA PADNA promotes bupivacaine-induced neurotoxicity by miR-194/FBXW7 axis - Fan Yuning; Chen Liang; Wang Tenghuan; Nan Zhenhua; Gong Shengkai (BMC, 2020)
Abstract Background The aim of the study was to explore the function and mechanism of lincRNA PADNA in bupivacaine-induced neurotoxicity. Methods Mouse DRG neurons were cultured in vitro and treated with bupivacaine to establish a neurotoxicity model. Caspase3 activity, cell viability, and TUNEL assays were analyzed to assess the role of lincRNA PADNA. A dual-luciferase reporter assay was used to determine the binding target of lincRNA PANDA. Results The expression of lincRNA PADNA was significantly increased with increasing concentrations of bupivacaine. Functional analysis revealed that knockdown of lincRNA PADNA increased caspase3 activity and inhibited cell viability. Western blot analysis showed that knockdown of lincRNA PADNA promoted cleaved caspase3 levels. We also revealed that lincRNA PADNA may bind with miR-194. Knockdown of miR-194 rescued the function of lincRNA PADNA, suggesting that lincRNA PADNA may sponge miR-194. In addition, we provided new evidence that the lincRNA PADNA/miR-194/FBXW7 axis plays an important role in the neurotoxicity process. Conclusion We performed comprehensive experiments to verify the function and mechanism of lincRNA PADNA in bupivacaine-induced neurotoxicity. Our study provides new evidence and clues for the prevention of neurotoxicity.